2011
DOI: 10.2478/s11686-011-0006-1
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites of the Atlantic chub mackerel, Scomber colias Gmelin, 1789 from Canary Islands, Central North Atlantic, with comments on their relations with other Atlantic regions

Abstract: Eleven parasite taxa were found infecting 68 Atlantic chub mackerel, Scomber colias Gmelin, 1789 from the Canary Islands, Central North Atlantic. The most abundant parasites were the gill monogenean Pseudokuhnia minor (P = 54.4%), larval anisakid nematodes (P = 11.8%) in the body cavity, a larval tetraphyllidean infecting bile ducts (P = 8.8%) and didymozoid digeneans infecting the gills (P = 7.4%). No correlation between fish length and abundance of infection with these parasites was found. Within the Atlanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The results were compared with those of 10 localities of the Atlantic Ocean (Cremonte and Sardella 1997;Alves et al 2003;Shukhgalter 2004;Oliva et al 2008;Costa et al 2011) (Fig. 1, Table II), using both univariate and multivariate analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results were compared with those of 10 localities of the Atlantic Ocean (Cremonte and Sardella 1997;Alves et al 2003;Shukhgalter 2004;Oliva et al 2008;Costa et al 2011) (Fig. 1, Table II), using both univariate and multivariate analyses.…”
mentioning
confidence: 99%
“…sensu Shukhgalter (2004) and Nemathobothrium sp. sensu Costa et al (2011) #, Nematobothrium scombri is considered as Nematobothrium spp. sensu Cremonte and Sardella (1997) Unauthenticated Download Date | 5/10/18 2:51 PM Eight species of parasites were found in the head of the 30 specimens of S. colias examined (Table II): Grubea cochlear Diesing, 1858, Kuhnia scombercolias Nasir et Fuentes Zambrano, 1983, K. scombri (Kuhn, 1829, Pseudokuhnia minor (Goto, l894), Nematobothrium cf.…”
mentioning
confidence: 99%
“…Scomber is a genus of ocean-dwelling mackerels, and the four species of Scomber are commonly infected with Anisakid nematodes. Fish with a high recorded variability of species of the genus Anisakis infection was the spotted mackerel, S. australasicus (A. pegreffii, A. simplex s.s., A. typica, A. paggiae, A. physeteris, A. brevispiculata and a recombinant genotype), followed by chub mackerel, Scomber japonicas (A. pegreffii, A. simplex s.s., A. typica, A. physeteris, A. ziphidarum and a recombinant genotype), atlantic chub mackerel, Scomber colias (A. pegreffii, A. physeteris, A. nascettii and A. typica), and atlantic mackerel, Scomber scombrus (A. pegreffii, A. simplex s.s. and A. physeteris) (Abollo et al, 2001;Bak et al, 2014;Chen et al, 2014;Costa et al, 2011;Pontes et al, 2005). A. simplex s.s. or A. pegreffii were found in four species of Scomber, and they are the most common cause of human anisakiasis.…”
Section: Discussionmentioning
confidence: 95%
“…Many of these prey items are known as intermediate/paratenic hosts of anisakid nematodes (Hays et al, 1998;Rello et al, 2009), and several studies have shown that chub mackerel in different areas are infected with diverse species of anisakid nematodes (Abattouy et al, 2011;Shukhgalter, 2004;Suzuki et al, 2010). In addition, other scombrid fish species such as S. colias, S. australasicus, and S. scombrus are known to be infected with various anisakid nematodes species (Chou et al, 2011;Costa et al, 2011;Gutierrez-Galindo et al, 2010). Given that these scombrid fish are commercially important fish species, anisakid nematode larvae can be accidentally transmitted to humans when the fish are consumed raw or undercooked.…”
Section: Discussionmentioning
confidence: 97%